MATH SOLVE

4 months ago

Q:
# Only answer if you are 100% sure

Accepted Solution

A:

[tex] \frac{2 {y}^{2} - 7y - 15 }{y - 5} = 2y \\ remainder \: \frac{2 {y}^{2} - 7y - 15 }{ - (2{y }^{2} - 10y + 0)} \\ = 3y - 15[/tex]

[tex] \frac{3y - 15}{y - 5} = 3 \\ remainder \: \frac{3y - 15}{ - (3y - 15)} = 0[/tex]

So the quotient is : 2y + 3, with no remainder

[tex] \frac{2 {y}^{2} - 7y - 15 }{y - 5} = 2y \\ remainder \: \frac{2 {y}^{2} - 7y - 15 }{ - (2{y }^{2} - 10y + 0)} \\ = 3y - 15[/tex]

[tex] \frac{3y - 15}{y - 5} = 3 \\ remainder \: \frac{3y - 15}{ - (3y - 15)} = 0[/tex]

So the quotient is : 2y + 3, with no remainder